Analisis Strategi Kualitas Kelembagaan Koperasi Pada Dinas Koperasi Provinsi Sumatera Utara - Putri Hermayani; Muhammad Arif (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The Department of Cooperatives and SMEs of North Sumatra Province, of course, has a strategy so that cooperatives in North Sumatra Province continue to grow and develop. This study aims to determine the strategy for improving the quality of cooperative institutions, identify the driving and inhibiting factors. Formulate a concept map of the problem of improving the quality of cooperative institutions. This research is a case study qualitative research. The focus of the research is on the steps/strategies of the North Sumatra Province cooperative service in improving the quality of cooperative institutions, including: licensing and cooperative institutions, cooperative empowerment, supervision and inspection of cooperatives. The results of the study indicate that there are stages of strategy in an effort to improve the quality of cooperative institutions. So that from the results of the analysis in each field has an inseparable link in its efforts to improve the quality of existing cooperative institutions in North Sumatra Province. targets, resulting in strategic recommendations given Progressive, meaning that the organization is in prime and stable condition so that it is possible to continue to develop, increase growth and achieve maximum progress. This situation is very advantageous, because the power possessed can be utilized for the opportunities that exist.